Carbon tax on milk products and the exact consumer welfare measure in emerging economies - Jasmin Wehner; Xiaohua Yu (Agribusiness, 2023)
Current milk prices do not account for the emissions, environmental externalities, and the excessive resource use that occur during milk production. Imposing a “carbon tax on food” can be a very effective climate change mitigation policy and the ultimate distributional effect depends heavily on the way the tax is implemented. To offset the regressive financial effect, redistribution measures need to be designed and the financial welfare loss can serve as a first orientation for designing these redistribution measures. Current literature mainly uses estimated elasticities from empirical demand systems to approximate the welfare change which can lead to a substantial bias if the tax rate is sufficiently large. In contrast, we calculate the welfare change by using the Exact Consumer Welfare of a carbon tax on milk for selected emerging economies. We show that on average, consumers in upper-middle-income economies would face a financial welfare loss of 19.4–176.9 USD (in the value of 2017) measured by the compensating variation (CV), depending on the tax scenario. Among a set of 16 emerging economies, consumers in Argentina (ARG) and Türkiye (TUR) face the highest financial welfare losses. We also find that discrepancies between the Exact Consumer Welfare and the consumer surplus are very small. [EconLit Citations: Q11, Q18].
Keywords: 630; carbon tax; consumer welfare change; emerging economies; milk consumption